Preparation method of silicon carbide reinforced aluminum-based composite material for electronic packaging

By pre-oxidizing and vacuum micro-evaporation titanium plating on the surface of silicon carbide particles, combined with microarc oxidation technology, the TiC/Ti5Si3-Al interface layer and Al2O3 coating are formed, the thermal conductivity and resistance of silicon carbide-enhanced aluminum-based composite materials are solved. The problem of insufficient corrosion performance achieves efficient heat dissipation and corrosion resistance.

CN119464821APending Publication Date: 2025-02-18SUZHOU HATENG TECH CO LTD

Patent Information

Application Number
CN202411642937.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing silicon carbide-reinforced aluminum-based composite materials have problems with insufficient thermal conductivity and corrosion resistance in electronic packaging, which leads to the inability of the chip to effectively dissipate heat and affects performance.

Method used

By pre-oxidizing and vacuum micro-evaporation titanium plating treatment on the surface of silicon carbide particles, the interface combination between SiC particles and aluminum matrix is ​​improved, and combined with microarc oxidation technology, the TiC/Ti5Si3-Al interface layer and Al2O3 coating are formed to improve the thermal conductivity of the material Performance and corrosion resistance.

Benefits of technology

It significantly improves the thermal conductivity and corrosion resistance of silicon carbide-enhanced aluminum-based composite materials, can effectively solve the failure problem caused by overheating in electronic packaging, and meet high heat dissipation requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of metal-based composite materials, and discloses a preparation method of a silicon carbide reinforced aluminum-based composite material for electronic packaging, the method that pre-oxidation is conducted on the surfaces of silicon carbide particles first and then vacuum micro-evaporation titanium plating is conducted is adopted, the wettability with an Al matrix is obviously improved, generation of an interface reaction brittle product Al4C3 is inhibited, and the performance of the silicon carbide reinforced aluminum-based composite material is improved. Defects such as gaps in the composite material are reduced, and the mechanical property of the composite material is improved; the silicon carbide reinforced aluminum-based composite material is prepared by adopting a non-pressure infiltration method, so that the production time is obviously shortened, infiltration can be successful by taking a small amount of time, and the process is stable; the interface phase TiC / Ti5Si3-Al coating not only improves the electrical conductivity and thermal conductivity of the silicon carbide powder, but also enhances the adhesive force of the silicon carbide powder and an aluminum base; al2O3 is gradually adsorbed and deposited on the surface of the material by adopting a micro-arc oxidation process, so that the corrosion resistance of the aluminum silicon carbide composite material is enhanced, and the requirements of a contemporary packaging material on high heat dissipation and corrosion resistance can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal-based composite materials, and in particular to a method for preparing a silicon carbide reinforced aluminum-based composite material for electronic packaging. Background Art

[0002] As microelectronic devices develop towards high performance, light weight and miniaturization, electronic packaging is an important technology for protecting electronic devices, achieving electrical connections, dissipating heat, improving mechanical strength and other key functions. The selection and research of materials are increasingly valued. Traditional packaging materials include silicon substrates, metal substrates and ceramic substrates. Silicon and ceramic substrates are difficult to process, high cost and low thermal conductivity. The thermal expansion coefficient of metal substrates does not match that of microelectronic chips, and thermal stress will be generated and warped during use. Therefore, these traditional packaging materials are difficult to meet the demanding requirements of packaging substrates. Silicon carbide reinforced aluminum-based composites are a ceramic particle reinforced metal-based composite material that has the excellent properties of both metal and ceramic. However, the complexity and limitations of the preparation process lead to insufficient material density and thermal conductivity. At present, 30% of chips cannot perform their performance normally because the packaging materials cannot effectively dissipate heat. Therefore, the current focus is on how to optimize the preparation method of silicon carbide reinforced aluminum-based composites to improve the thermal conductivity of composite materials.

[0003] Due to the small size of SiC particles, high specific surface energy, easy accumulation and uneven dispersion, the discrete distribution state of SiC particles in the aluminum alloy matrix is ​​seriously affected and damaged, and the wettability with the aluminum matrix is ​​poor. There will be a large number of micropores in the prepared composite material, which is easy to crack under the action of external stress. In addition, the weak bonding interface between SiC particles and the aluminum matrix will debond during service, which limits the further application and development of SiC particle reinforced aluminum-based composite materials. In addition, SiC particles have irregular shapes and many sharp corners. The material is prone to rupture at the interface due to stress concentration, and the load transfer effect is poor. During the preparation of parts, the probability of stress concentration will increase, and the surface of the matrix will be damaged, which is not conducive to the processing and application of formed parts.

[0004] The addition of the second phase in the composite material will make the Al-based composite material present a non-uniform structure, so that the corrosion performance of the SiC / Al composite material is weaker than that of the matrix. With the gradual development of SiC / Al composite materials, the application of this material needs to face more and more complex and harsh service conditions, and higher requirements are placed on its corrosion resistance; Patent No. CN104451240B discloses a preparation method of a silicon carbide reinforced aluminum-based composite material for electronic packaging, in which a layer of copper is coated on the surface of silicon carbide, which greatly improves the wettability between the reinforced particles and the aluminum matrix, and solves the failure problem caused by overheating in current electronic packaging products, but does not improve the corrosion resistance of the metal-based composite material; the present invention aims to achieve surface modification of SiC particles and micro-arc oxidation treatment of the composite material, which significantly improves the thermal conductivity and corrosion resistance of the composite material, and promotes the development of electronic equipment and the improvement of integrated circuits. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a method for preparing a silicon carbide reinforced aluminum-based composite material for electronic packaging, thereby overcoming the difficulty in dispersing silicon carbide particles in the aluminum matrix and the failure problem caused by overheating of current electronic packaging products, and further improving the corrosion resistance of the aluminum-based composite material.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a silicon carbide reinforced aluminum-based composite material for electronic packaging comprises the following steps:

[0008] Step (1), preparation of SiC / Al composite material: in an argon atmosphere, the vacuum micro-evaporated titanium-coated SiC is ground evenly, loaded into a breathable ceramic boat, and after vibration compaction, the aluminum alloy is placed on top of the compacted vacuum micro-evaporated titanium-coated SiC powder, placed in an infiltration device, heated to 950-1100° C. by gradient heating, and pressureless infiltration is performed for 1-2 hours, and air-cooled until completely solidified to obtain a SiC / Al composite material.

[0009] Step (2), micro-arc oxidation of SiC / Al composite material: the SiC / Al composite material is placed in a sodium phosphate aqueous solution, degreased at 75-90°C for 5-10 min, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 1-5 min, ultrasonically cleaned and dried, immersed in a micro-arc oxidation electrolyte, and subjected to micro-arc oxidation treatment, using bidirectional pulsed alternating current with a current density of 10-15 A / dm 2 , the forward voltage is 200-500V, the negative voltage is 20-140V, the oxidation processing frequency is 180-220Hz, the rated power is 1.8-2.2kW, the duty cycle is 30-50%, and a silicon carbide reinforced aluminum-based composite material for electronic packaging is obtained.

[0010] Furthermore, the gradient heating process in step (1) is: first heating to 200-300°C and keeping warm for 5-10 minutes, then heating to 500-600°C and keeping warm for 10-20 minutes, then heating to 750-900°C and keeping warm for 25-40 minutes, and finally heating to 950-1100°C.

[0011] Furthermore, in step (1), the particle size of the vacuum micro-evaporated titanium-coated SiC after grinding is 5-10 μm, the purity of the aluminum alloy is not less than 99.8%, and the volume fraction of SiC in the SiC / Al composite material is 50-70%.

[0012] Furthermore, in step (2), the micro-arc oxidation electrolyte is an alkaline electrolyte, which is prepared by dissolving sodium hydroxide and sodium aluminate in 1L of deionized water in a mass ratio of 10:1 and stirring evenly.

[0013] Furthermore, in step (2), the micro-arc oxidation time is 5-25 min.

[0014] Furthermore, the method for preparing titanium-coated SiC by vacuum micro-evaporation in step (1) comprises the following steps:

[0015] Step S1, pre-oxidation of the surface of SiC nanoparticles: stirring the SiC nanoparticles in a boiling sodium hydroxide solution for 10-20 minutes, cooling and precipitating, washing with deionized water until the pH is neutral, placing in a box-type resistance furnace, first heating to 180-220° C. for 5-10 minutes, then heating to 750-850° C. for 8-15 minutes, and finally heating to 900-1000° C. for 2-4 hours, cooling with the furnace, grinding and crushing to obtain pre-oxidized SiC nanoparticles.

[0016] Step S2, titanium plating on the surface of SiC nanoparticles: the pre-oxidized SiC nanoparticles are stirred in a boiling nitric acid solution for 5-10 minutes, deionized and cleaned by centrifugation, placed in a planetary ball mill, and metal titanium powder is added. The mixed materials are mixed at a rotation speed of 300-450r / min for 3-5 hours, and the mixed powder is vacuum micro-evaporated and titanium-plated in a vacuum sintering furnace, kept warm for 3-8 hours, cooled in the furnace, and sieved to obtain vacuum micro-evaporated titanium-plated SiC.

[0017] Furthermore, the concentration of the sodium hydroxide solution in step S1 is 2-3.5 mol / L.

[0018] Furthermore, in step S2, the mass ratio of pre-oxidized SiC nanoparticles to metal titanium powder is 100:(35-50).

[0019] Furthermore, the mass fraction of the nitric acid solution in step S2 is 60-75%.

[0020] Furthermore, in step S2, the temperature of the vacuum micro-evaporation titanium plating is set to 750-900° C. and the gas pressure is 0.5-1 MPa.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adopts a method of pre-oxidizing the surface of silicon carbide particles and then vacuum micro-evaporating titanium, which can change the irregular shape of silicon carbide particles and improve the dispersibility of silicon carbide powder; the SiC subjected to pre-oxidation is subjected to a high-temperature staged oxidation reaction to generate SiO2, which is easy to undergo a series of interface reactions with the aluminum alloy matrix, and promotes the discrete distribution of SiC particles. The composite material has less stress concentration and better load transfer effect.

[0023] 2. After pre-oxidation and vacuum micro-evaporation titanium plating treatment, a compound coating containing two phases of TiC and Ti5Si3 can be generated on the SiC surface, forming a close chemical bond with SiC. The titanium element preferentially reacts with SiC to form a TiC / Ti5Si3-Al interface layer, reducing the wetting angle between the two, significantly improving the wettability with the Al matrix, inhibiting the formation of the brittle product Al4C3 of the interface reaction, and reducing defects such as voids in the composite material. The more uniform the distribution of SiC particles in the Al matrix, the higher the hardness value of the composite material, thereby improving the mechanical properties of the composite material.

[0024] 3. The present invention adopts a pressureless infiltration method to prepare silicon carbide reinforced aluminum-based composite materials. The Al matrix is ​​placed in a controlled atmosphere furnace and heated until it is higher than the melting temperature of Al. Without applying external pressure, the Al liquid will penetrate into the SiC particle layer by itself. The pressureless infiltration method can be used to prepare products with different performances as needed, which significantly reduces the production time. It only takes a short time to successfully infiltrate, and the process is stable.

[0025] 4. The number of sites for mutual wetting reaction between titanium and aluminum increases, thus forming a uniform and clean interface phase TiC / Ti5Si3-Al coating at the interface, making the interface bonding tighter. This coating not only improves the electrical conductivity and thermal conductivity of silicon carbide powder, but also enhances its adhesion to the aluminum base, thereby improving the degree of interface bonding. The thermal conductivity is also significantly improved, which is much greater than other interface transition layers. It can well solve the failure problem caused by overheating in current electronic packaging products and meet the high heat dissipation requirements of contemporary packaging materials.

[0026] 5. Using the micro-arc oxidation process, the Al2O3 phase content in the film layer continues to increase with the extension of the micro-arc oxidation time, and is gradually adsorbed and deposited on the surface of the material to form a uniform and dense coating, which enhances the corrosion resistance of the aluminum silicon carbide composite material and can effectively block the corrosive media in the external environment, thereby extending the service life of the aluminum-based composite material. DETAILED DESCRIPTION

[0027] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Unless otherwise indicated, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.

[0028] The micro-arc oxidation electrolyte is an alkaline electrolyte, which is prepared by dissolving sodium hydroxide and sodium aluminate in 1L of deionized water at a mass ratio of 10:1 and stirring evenly.

[0029] Example 1

[0030] In an argon atmosphere, SiC nanoparticles are evenly ground and loaded into a breathable ceramic boat. After vibration compaction, the aluminum alloy is placed on top of the compacted SiC nanoparticles and placed in an infiltration device. The mixture is first heated to 250°C and kept for 8 minutes, then heated to 550°C and kept for 15 minutes, then heated to 800°C and kept for 35 minutes, and finally heated to 1050°C for pressureless infiltration for 2 hours. The mixture is air-cooled to complete solidification, wherein the particle size of the vacuum micro-evaporated titanium-coated SiC after grinding is 8 μm, the purity of the aluminum alloy is not less than 99.8%, and the volume fraction of SiC in the SiC / Al composite material is 50%, thereby obtaining a SiC / Al composite material.

[0031] Example 2

[0032] (1) SiC nanoparticles were stirred in a boiling sodium hydroxide solution with a concentration of 2.5 mol / L for 15 min, cooled and precipitated, washed with deionized water until the pH was neutral, placed in a box-type resistance furnace, first heated to 200°C for 9 min, then raised to 800°C for 12 min, and finally raised to 950°C for 3 h, cooled with the furnace, ground and crushed to obtain pre-oxidized SiC nanoparticles.

[0033] (2) Preparation of SiC / Al composite materials: Under an argon atmosphere, pre-oxidized SiC nanoparticles were ground evenly and loaded into a breathable ceramic boat. After vibration compaction, aluminum alloy was placed on top of the compacted pre-oxidized SiC nanoparticles and placed in an infiltration device. The mixture was first heated to 300°C for 10 min, then raised to 600°C for 20 min, then raised to 750°C for 40 min, and finally raised to 1100°C for pressureless infiltration for 1 h. The mixture was air-cooled until completely solidified. The particle size of the pre-oxidized SiC nanoparticles after grinding was 10 μm. The purity of the aluminum alloy was not less than 99.8%. The volume fraction of SiC in the SiC / Al composite material was 50%, thereby obtaining a SiC / Al composite material.

[0034] Example 3

[0035] (1) Pre-oxidation of SiC nanoparticle surface: SiC nanoparticles were stirred in a boiling 3.5 mol / L sodium hydroxide solution for 10 min, cooled and precipitated, washed with deionized water until the pH was neutral, placed in a box-type resistance furnace, first heated to 220°C for 5 min, then raised to 850°C for 8 min, and finally raised to 1000°C for 2 h, cooled and ground to obtain pre-oxidized SiC nanoparticles.

[0036] (2) Titanium coating on the surface of SiC nanoparticles: 20 g of pre-oxidized SiC nanoparticles were stirred in a boiling nitric acid solution with a mass fraction of 65% for 10 min, deionized, cleaned and centrifuged, placed in a planetary ball mill, 9 g of metal titanium powder was added, and the mixture was mixed at a speed of 400 r / min for 5 h. The mixed powder was vacuum micro-evaporated and titanium-coated in a vacuum sintering furnace at a temperature of 850°C and an air pressure of 1 MPa. The mixture was kept warm for 5 h, cooled in the furnace, and sieved to obtain vacuum micro-evaporated titanium-coated SiC.

[0037] (3) Preparation of SiC / Al composite materials: Under an argon atmosphere, the vacuum micro-evaporated titanium-coated SiC was ground evenly and loaded into a breathable ceramic boat. After vibration compaction, the aluminum alloy was placed on top of the compacted vacuum micro-evaporated titanium-coated SiC powder and placed in an infiltration device. The mixture was first heated to 200°C and kept warm for 10 min, then raised to 500°C and kept warm for 20 min, then raised to 750°C and kept warm for 25 min, and finally raised to 1100°C for pressureless infiltration for 2 h. The mixture was air-cooled until completely solidified. The particle size of the vacuum micro-evaporated titanium-coated SiC after grinding was 5 μm, the purity of the aluminum alloy was not less than 99.8%, and the volume fraction of SiC in the SiC / Al composite material was 50%. Thus, a SiC / Al composite material was obtained.

[0038] Tensile performance test: according to GB / T 6397-1986, tensile specimens were prepared and tensile tests were carried out using a tensile testing machine at a tensile rate of 1 mm / min.

[0039] Hardness test: The formed aluminum-based composite material samples were cut and processed into 10mm×10mm×3mm hardness test pieces, and the hardness values ​​were obtained by measuring 8 points with a microhardness tester.

[0040] Wear resistance test: The composite material was subjected to a sliding friction test using a friction and wear testing machine with a pressure of 25 N, a rotation speed of 120 r / min, and a time of 30 min.

[0041] Table 1 Tensile properties and wear test

[0042] Tensile strength(MPa) Hardness (HV) Wear amount (mg) Example 1 224.5 62.4 1.83 Example 2 312.3 89.5 1.36 Example 3 407.1 105.6 0.52

[0043] It can be seen from the test results in the above table that the SiC surface in Example 1 is untreated, and its interface bonding with the Al matrix is ​​poor, which is easy to produce harmful impurities, and the mechanical properties of the composite material are damaged; the SiC subjected to pre-oxidation treatment in Example 2, SiO2 generated by high-temperature staged oxidation reaction, is easy to undergo a series of interface reactions with the aluminum alloy matrix, which promotes the discrete distribution degree of SiC particles, and the composite material has less stress concentration and better load transfer effect; after pre-oxidation and vacuum micro-evaporation titanium plating treatment, the tensile strength of the SiC in Example 3 reaches 407.1MPa, because a compound coating containing TiC and Ti5Si3 dual phases is generated on the SiC surface, forming a close chemical bond with SiC, and the titanium element preferentially reacts with SiC to generate a TiC / Ti5Si3-Al interface layer, reducing the wetting angle between the two, significantly improving the wettability with the Al matrix, inhibiting the generation of the brittle product Al4C3 of the interface reaction, reducing defects such as voids in the composite material, and the more uniform the distribution of SiC particles in the Al matrix, the higher the hardness value of the composite material, thereby improving the mechanical properties of the composite material.

[0044] The interface bonding strength between SiC and Al matrix after pre-oxidation and titanium plating is improved, the load of the composite material can be effectively transferred to the reinforcement during deformation, and the interface debonding is effectively improved. Therefore, the abrasive wear degree of the composite material after pre-oxidation and titanium plating is reduced, and the wear resistance is significantly improved.

[0045] Example 4

[0046] The difference between this embodiment and implementation embodiment 3 is that the volume fraction of SiC in the SiC / Al composite material in step (3) is 55%, and other conditions remain the same.

[0047] Example 5

[0048] The difference between this embodiment and implementation embodiment 3 is that the volume fraction of SiC in the SiC / Al composite material in step (3) is 60%, and other conditions remain the same.

[0049] Example 6

[0050] The difference between this embodiment and implementation embodiment 3 is that the volume fraction of SiC in the SiC / Al composite material in step (3) is 65%, and other conditions remain the same.

[0051] Example 7

[0052] The difference between this embodiment and implementation embodiment 3 is that the volume fraction of SiC in the SiC / Al composite material in step (3) is 70%, and other conditions remain the same.

[0053] Thermal expansion coefficient test: The thermal expansion coefficient of the aluminum-based diamond composite material was measured using a static thermomechanical analyzer.

[0054] Thermal conductivity test: The thermal conductivity of aluminum-based diamond composites was tested using a laser thermal conductivity analyzer. The test specimen was a cylinder with a size of

[0055] Table 2 Thermal conductivity test

[0056] <![CDATA[Coefficient of thermal expansion (10 -6 K)]]> Thermal conductivity (W / m·K) Example 3 15.2 521 Example 4 11.5 556 Example 5 8.3 588 Example 6 5.8 613 Example 7 4.6 622

[0057] Silicon carbide itself has a high thermal conductivity and can effectively dissipate heat. However, the needle-shaped reactant A14C3 formed at the interface between Al and SiC will reduce the thermal conductivity of the SiC / Al composite material. As the content of titanium-plated SiC on the surface of the composite material increases, the number of sites for mutual wetting reactions between titanium and aluminum increases, thereby forming a uniform and clean interface phase TiC / Ti5Si3-Al coating at the interface, making the interface bonding tighter. This coating not only improves the electrical conductivity and thermal conductivity of silicon carbide powder, but also enhances its adhesion to the aluminum base, thereby improving the degree of interface bonding. The thermal conductivity is also significantly improved, which is much greater than other interface transition layers. It can well solve the failure problem caused by overheating in current electronic packaging products and can meet the high heat dissipation requirements of contemporary packaging materials.

[0058] Example 8

[0059] The SiC / Al composite material (prepared in Example 6) was placed in a sodium phosphate aqueous solution, degreased at 85°C for 6 min, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 3 min, ultrasonically cleaned and dried, immersed in a micro-arc oxidation electrolyte, and subjected to micro-arc oxidation treatment using a bidirectional pulsed alternating current with a current density of 12 A / dm 2 , the forward voltage is 200V, the negative voltage is 20V, the oxidation processing frequency is 200Hz, the rated power is 2kW, the duty cycle is 40%, and the micro-arc oxidation time is 5min to obtain a silicon carbide reinforced aluminum-based composite material for electronic packaging.

[0060] Example 9

[0061] The SiC / Al composite material (prepared in Example 6) was placed in a sodium phosphate aqueous solution, degreased at 75°C for 10 min, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 5 min, ultrasonically cleaned and dried, immersed in a micro-arc oxidation electrolyte, and subjected to micro-arc oxidation treatment using a bidirectional pulsed alternating current with a current density of 10 A / dm 2, the forward voltage is 300V, the negative voltage is 50V, the oxidation processing frequency is 180Hz, the rated power is 1.8kW, the duty cycle is 30%, and the micro-arc oxidation time is 10min to obtain a silicon carbide reinforced aluminum-based composite material for electronic packaging.

[0062] Example 10

[0063] The SiC / Al composite material (prepared in Example 6) was placed in a sodium phosphate aqueous solution, degreased at 90°C for 5 min, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 1 min, ultrasonically cleaned and dried, immersed in a micro-arc oxidation electrolyte, and subjected to micro-arc oxidation treatment using a bidirectional pulsed alternating current with a current density of 15 A / dm 2 , the forward voltage is 400V, the negative voltage is 80V, the oxidation processing frequency is 220Hz, the rated power is 2.2kW, the duty cycle is 50%, and the micro-arc oxidation time is 15min to obtain a silicon carbide reinforced aluminum-based composite material for electronic packaging.

[0064] Embodiment 11

[0065] The SiC / Al composite material (prepared in Example 6) was placed in a sodium phosphate aqueous solution, degreased at 80°C for 7 minutes, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 4 minutes, ultrasonically cleaned and dried, and immersed in a micro-arc oxidation electrolyte for micro-arc oxidation treatment using a bidirectional pulsed alternating current with a current density of 14 A / dm 2 , the forward voltage is 500V, the negative voltage is 110V, the oxidation processing frequency is 210Hz, the rated power is 2.1kW, the duty cycle is 45%, and the micro-arc oxidation time is 20min to obtain a silicon carbide reinforced aluminum-based composite material for electronic packaging.

[0066] Example 12

[0067] The SiC / Al composite material (prepared in Example 6) was placed in a sodium phosphate aqueous solution, degreased at 90°C for 7 minutes, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 3 minutes, ultrasonically cleaned and dried, and immersed in a micro-arc oxidation electrolyte for micro-arc oxidation treatment using a bidirectional pulsed alternating current with a current density of 12 A / dm 2 , the forward voltage is 500V, the negative voltage is 140V, the oxidation processing frequency is 200Hz, the rated power is 1.9kW, the duty cycle is 40%, and the micro-arc oxidation time is 25min to obtain a silicon carbide reinforced aluminum-based composite material for electronic packaging.

[0068] Corrosion resistance test: The prepared composite material was placed in a sodium chloride solution with a mass fraction of 3.5% and immersed for 7 days, and the corrosion weight loss value was calculated.

[0069] Table 3 Corrosion resistance test

[0070] Corrosion weight loss value (g) Example 6 0.2158 Example 8 0.0830 Example 9 0.0785 Example 10 0.0564 Embodiment 11 0.0334 Example 12 0.0312

[0071] From the test results in the above table, it can be seen that with the increase of micro-arc oxidation time, the corrosion resistance of the composite material gradually increases. This is because in the sodium aluminate electrolyte system of micro-arc oxidation, the main anion in the solution is AlO2 - , under the action of strong electric field, AlO2 - It is easy to react with water to generate Al(OH)3, and a large amount of deposition covers the surface of the sample. When the current passes through the anode surface, the covering layer will generate a lot of heat, thereby promoting the dehydration of Al(OH)3 into Al2O3, and Al2O3 has chemical corrosion resistance, because the Al2O3 phase content in the film layer increases with the extension of micro-arc oxidation time, and gradually adsorbs and deposits on the surface of the material to form a uniform and dense coating, which enhances the corrosion resistance of the aluminum silicon carbide composite material and can effectively block the corrosive medium in the external environment, thereby extending the service life of the material.

[0072] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. A method for preparing a silicon carbide reinforced aluminum-based composite material for electronic packaging, characterized in that: The preparation method comprises the following steps: Step (1), preparation of SiC / Al composite material: in an argon atmosphere, vacuum micro-evaporated titanium-coated SiC is ground uniformly, loaded into a breathable ceramic boat, and vibrated to compact, and then aluminum alloy is placed on top of the compacted vacuum micro-evaporated titanium-coated SiC powder, placed in an infiltration device, heated to 950-1100° C. by gradient heating, and pressureless infiltration is performed for 1-2 hours, and air-cooled until completely solidified to obtain a SiC / Al composite material; Step (2), micro-arc oxidation of SiC / Al composite material: the SiC / Al composite material is placed in a sodium phosphate aqueous solution, degreased at 75-90°C for 5-10 min, then placed in a hydrochloric acid aqueous solution, pickled at room temperature for 1-5 min, ultrasonically cleaned and dried, immersed in a micro-arc oxidation electrolyte, and subjected to micro-arc oxidation treatment, using bidirectional pulsed alternating current with a current density of 10-15 A / dm 2 , the forward voltage is 200-500V, the negative voltage is 20-140V, the oxidation processing frequency is 180-220Hz, the rated power is 1.8-2.2kW, the duty cycle is 30-50%, and a silicon carbide reinforced aluminum-based composite material for electronic packaging is obtained.

2. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 1, characterized in that: The gradient heating process in step (1) is: firstly heat to 200-300°C and keep warm for 5-10 minutes, then heat to 500-600°C and keep warm for 10-20 minutes, then heat to 750-900°C and keep warm for 25-40 minutes, and finally heat to 950-1100°C.

3. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 1, characterized in that: In the step (1), the particle size of the vacuum micro-evaporated titanium-coated SiC after grinding is 5-10 μm, the purity of the aluminum alloy is not less than 99.8%, and the volume fraction of SiC in the SiC / Al composite material is 50-70%.

4. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 1, characterized in that: The micro-arc oxidation electrolyte in step (2) is an alkaline electrolyte, which is prepared by dissolving sodium hydroxide and sodium aluminate in 1 L of deionized water at a mass ratio of 10:1 and stirring evenly.

5. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 1, characterized in that: The micro-arc oxidation time in step (2) is 5-25 minutes.

6. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 1, characterized in that: The method for preparing titanium-plated SiC by vacuum micro-evaporation in step (1) comprises the following steps: Step S1, pre-oxidation of the surface of SiC nanoparticles: stirring the SiC nanoparticles in a boiling sodium hydroxide solution for 10-20 minutes, cooling and precipitating, washing with deionized water until the pH is neutral, placing in a box-type resistance furnace, first heating to 180-220° C. for 5-10 minutes, then heating to 750-850° C. for 8-15 minutes, and finally heating to 900-1000° C. for 2-4 hours, cooling with the furnace, grinding and crushing to obtain pre-oxidized SiC nanoparticles; Step S2, titanium plating on the surface of SiC nanoparticles: the pre-oxidized SiC nanoparticles are stirred in a boiling nitric acid solution for 5-10 minutes, deionized and cleaned by centrifugation, placed in a planetary ball mill, and metal titanium powder is added. The mixed materials are mixed at a rotation speed of 300-450r / min for 3-5 hours, and the mixed powder is vacuum micro-evaporated and titanium-plated in a vacuum sintering furnace, kept warm for 3-8 hours, cooled in the furnace, and sieved to obtain vacuum micro-evaporated titanium-plated SiC.

7. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 6, characterized in that: The concentration of the sodium hydroxide solution in step S1 is 2-3.5 mol / L.

8. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 6, characterized in that: In the step S2, the mass ratio of the pre-oxidized SiC nanoparticles to the metal titanium powder is 100:(35-50).

9. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 6, characterized in that: The mass fraction of the nitric acid solution in step S2 is 60-75%.

10. The method for preparing the silicon carbide reinforced aluminum-based composite material for electronic packaging according to claim 6, characterized in that: In the step S2, the temperature of the vacuum micro-evaporation titanium plating is set to 750-900° C. and the gas pressure is 0.5-1 MPa.

Citation Information

Patent Citations

  • A preparation method of silicon carbide reinforced aluminum matrix composite material for electronic packaging

    CN104451240B

Cited By

  • Aluminum-based silicon carbide composite battery shell and preparation method thereof, battery and electronic equipment

    CN121035464A

  • Powder metallurgy preparation method for silicon carbide aluminum-based material capable of regulating and controlling anisotropy

    CN121826424A